ANÁLISE DE MANUAIS DE USO, OPERAÇÃO E MANUTENÇÃO DE EDIFICAÇÕES HABITACIONAIS COM FOCO NA NORMA DE DESEMPENHO - Pallaoro, Ana Maria; Roscoff, Nathalia dos Santos; Costella, Monike de Medeiros; Lantelme, Elvira Maria Vieira; Costella, Marcelo Fabiano (ENCONTRO NACIONAL DE TECNOLOGIA DO AMBIENTE CONSTRUÍDO, 2018)
The performance standard NBR 15575 implemented important definitions of maintenance of the constructive systems, useful life and guarantee. Such as the standard is fairly new, still, haven't known if in the buildings already build was defined the maintenance plan and if the guarantee was established according to the standard. The objective of this study is to check if the user manuals of buildings are determining the guarantee and the needs of maintenance in order to keep the performance defined in design like according to NBR 15575-1 (ABNT, 2013). The research method consisted of a collection of user manuals of residential buildings that were started after the performance standard was published. It also was done a checklist to evaluate these manuals based on standards and researches about the subject. The evaluation of the user´s manuals showed that 93% of the constructions companies of the sample are determining the guarantees and 53% are presenting a maintenance program, but not complete. The results show that concepts related to performance and maintenance still need to be disseminated in the construction industry.